EFEKTIVITAS MANAJEMEN PARKIR DALAM PERATURAN BUPATI GIANYAR NOMOR 57 TAHUN 2018 DI KELURAHAN UBUD - Novita Dewi, Dewa Ayu; Sastra Wijaya, Komang Adi; Putri Wirantari, I Dewa Ayu (CITIZEN CHARTER, 2020)
ABSTRACT Gianyar Regent Regulation No. 57 of 2018 concerning Management and Engineering of Traffic and Road Transportation and Parking Lot in the Tourism Area of ??Ubud regulates parking management to realize good traffic order and management in Ubud. In this study the researher used a qualitative descriptive method. The purpose of this research is to find out how the role and optimization of policies made by the government based on these regulations of traffic in Ubud. The data collection techniques used by interviews with informants, observation in the object, and documentation Through the theory of Effectiveness according to Duncan (2008) with indicators of goal achievement, integration and adaptation These problems are mostly due to the lack of commitment from the regional government and the government's attention to the policies that have been implemented. Keywords: Policy, Effectiveness, Parking Management, Central Parking